Genital fistula: Successes, challenges and way forward in a facility specialization in fistula management in Bangladesh - Biswas, Nrionmoy; Biswas, Animesh (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To explore the success, challenges and way forward on genital fistula in Bangladesh. Methods: From the October 2017 to September 2018; total numbers of 125 genital fistula cases were identified through a community network system in Cox’s Bazar. Out of them, 101 cases come to hospital for the repair. For each of the patients, details case history was documented, clinical management reports also captured using structured forms. The study performed descriptive analysis using the case history and clinical management data. Results: Out of 101 cases admitted, 95% of cases were of obstetric, 3% iatrogenic, 1% traumatic and remaining 1% was congenital. Mean age was 31 (18-73) years. Mean duration of disease was 6 (0.1-53) Years. Most of them had urinary incontinence (86.1 %) and 11.9% had faecal incontinence where 2% had both. VVF was performed in most of the cases (78%), another 22% was RVF. Only of them 9.9% had complications, remaining discharged without any complications. Mean duration of hospital stay was 17 (4-29) days. Success rate was 86.1% and in 13.9 % of cases next surgery was advised. For all patients psychiatry counseling was given before and after surgery. However, the hospital doesn’t provide other rehabilitation or reintegration support, therefore, there was challenge to mainstream the women in the society or secure their social positions. Conclusions: Community surveillance followed by timely referral can improve obstetric fistula burden in Bangladesh. However, as clinical management, its equally important to restore the women’s dignity in the society with rehabilitation and reintegration. Challenges is still persisting in functional of the system and effective collaboration between the different ministry of the government of resolve the condition.